The Prevalence of Fluoroquinolone-Resistant E. coli in Animals and Animal Products: A Systematic Review and Meta-Analysis - Hadi Sedigh Ebrahim-Saraie; Mohammad Esmaeil Amini; Meysam Hasannejad-Bibalan; Ervin Zadgari; Arash Bakhshi (Journal of Medical Bacteriology)
Background:   Biological contamination of foods is a serious problem for human health. Animal and animal products may be contaminated by these biological and chemical contaminants. One of the most important causes of foodborne illness in humans is Escherichia coli. Fluoroquinolones can be used as a suitable treatment for enteric infections in food-producing livestock. We aimed to evaluate the current status of resistance of E. coli strains isolated from animals and animal products to fluoroquinolone in Iran. Methods:   A systematic search was conducted using the Web of Science, PubMed, Embase, Google Scholar, and Scopus databases from 2000 to Oct 2020. Nineteen studies were selected based on the inclusion criteria and analysis by Comprehensive Meta-Analysis. Results:    Based on the data analysis, The rates of antibiotic resistance in animal strains were as follows: Flumequine (75.1%), Enroﬂoxacin (55.2%), Danofloxacin (48.1%), Ciprofloxacin (48.4%), and Norfloxacin (52.9%). Next, the rates of quinolone resistance among E. coli strains isolated from animal products were Norfloxacin (45.5%), Ciprofloxacin (44.5%), and Enroﬂoxacin (60.9%). Based on the funnel plots and Egger's test, there was no significant publication bias. Conclusion:   We finally concluded that antibiotic resistance in commensal E. coli is related to the overuse of antibiotics in livestock, especially fluoroquinolones.